Characterization of metabolite profile in Phyllanthus niruri and correlation with bioactivity elucidated by nuclear magnetic resonance based metabolomics - Mediani, Ahmed; Abas, Faridah; Maulidiani, M.; Khatib, Alfi; Tan, Chin Ping; Ismail, Intan Safinar; Shaari, Khozirah; Ismail, Amin (MDPI, 2017)
Phyllanthus niruri is an important medicinal plant. To standardize the extract and guarantee its maximum benefit, processing methods optimization ought to be amenable and beneficial. Herein, three dried P. niruri samples, air (AD), freeze (FD) and oven (OD), extracted with various ethanol to water ratios (0%, 50%, 70%, 80% and 100%) were evaluated for their metabolite changes using proton nuclear magnetic resonance (1H-NMR)-based metabolomics approach. The amino acids analysis showed that FD P. niruri exhibited higher content of most amino acids compared to the other dried samples. Based on principal component analysis (PCA), the FD P. niruri extracted with 80% ethanol contained higher amounts of hypophyllanthin and phenolic compounds based on the loading plot. The partial least-square (PLS) results showed that the phytochemicals, including hypophyllanthin, catechin, epicatechin, rutin, quercetin and chlorogenic, caffeic, malic and gallic acids were correlated with antioxidant and α-glucosidase inhibitory activities, which were higher in the FD material extracted with 80% ethanol. This report optimized the effect of drying and ethanol ratios and these findings demonstrate that NMR-based metabolomics was an applicable approach. The FD P. niruri extracted with 80% ethanol can be used as afunctional food ingredient for nutraceutical or in medicinal preparation.